DESCRIPTION OF A NONLINEAR LINK IN A CONTROL SYSTEM WITH DISTRIBUTED PARAMETERS - I. V. Kaliberda; A. B. Chernyshev (Современная наука и инновации, 2022)
The problem of adequate representation of models of real objects in the form of systems of linear equations is shown. As a solution, a method of analysis and synthesis of this class of systems with a single nonlinear element is proposed. At the same time, the article uses the criterion of absolute stability of V.M. Popov. A description of a nonlinear block implemented in the form of an executive mechanism is given. The conclusion is made about the result of modeling deposits taking into account the nonlinear element.